Enhancing Competitive Advantage Through Marketing Strategies: A Multi-Site Study of Pakesang, Tanawan, Ummi Habibie - Safitri, Indri; Hermawan, Agus; Siswanto, Ely (PT. EQUATOR SINAR AKADEMIA, 2025)
Marketing strategy is the key to achieving sustainable competitive advantage, both for goods and services companies. This study aims to determine the marketing strategy in increasing competitive advantage in local potential SMEs in Ternate City, a multi-site case study on SMEs: Pakesang, Tanawan, and Ummi Habibie. Using a qualitative approach with a multisite case study method, this research explores the variations and similarities of phenomena in three locations. Data analysis techniques include SWOT analysis with IFAS matrix, EFAS, and SWOT diagram, as well as QSPM analysis to determine strategy priorities. Results show that the three SMEs have implemented the STP strategy and marketing mix with a focus on local culture-based product excellence and personalized service. All three were in a favorable position in the SWOT analysis, allowing for the implementation of an aggressive growth strategy. Key recommendations include optimizing digital channels, modernizing production tools, product differentiation, and strengthening local supply chains. Synergy between SMEs and local governments is also recommended to strengthen the business ecosystem.